2004
DOI: 10.1023/b:bile.0000044871.80632.f9
|View full text |Cite
|
Sign up to set email alerts
|

Improving the expression of mini-proinsulin in Pichia pastoris

Abstract: Increased expression of recombinant mini-proinsulin in Pichia pastoris in 2.5 l bioreactors was achieved by increasing the cultivation pH from 5.1 to 6.3, by decreasing the temperature from 28 to 22 degrees C, and by periodical addition of ammonium sulfate and EDTA to the culture broth. Using this procedure, mini-proinsulin reached nearly 0.3 g l(-1) in the culture supernatant after 160 h of growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…It was suggested that limited proteolysis can be attributed to the fact that the solubility of the proteases decreases upon the addition of (NH 4 ) 2 SO 4 by sulfate conjugation, leading to decrease of the total proteolytic activity in the culture supernatant. País-Chanfrau et al ( 2004 ) also reported an increased expression of recombinant mini-proinsulin in P. pastoris in bioreactors, achieved by, among others, periodical addition of ammonium sulfate. In this study, we describe the successful expression of Tt CBH7 in P. pastoris , under high osmotic pressure and increased salinity conditions.…”
Section: Discussionmentioning
confidence: 97%
“…It was suggested that limited proteolysis can be attributed to the fact that the solubility of the proteases decreases upon the addition of (NH 4 ) 2 SO 4 by sulfate conjugation, leading to decrease of the total proteolytic activity in the culture supernatant. País-Chanfrau et al ( 2004 ) also reported an increased expression of recombinant mini-proinsulin in P. pastoris in bioreactors, achieved by, among others, periodical addition of ammonium sulfate. In this study, we describe the successful expression of Tt CBH7 in P. pastoris , under high osmotic pressure and increased salinity conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The human mini-proinsulin is characterized by a C-chain peptide consisting of only 9 amino acids (21)(22)(23)(24), whereas the C-chain peptide of natural human proinsulin is made up of 35 amino acids. The bridge between B chain and A chain is only 16.12 Å, and 16 Å is the minimum distance between a five-AA protein; hence, a three to five amino acid should be able to connect the C terminal B chain and the N terminal A chain, forming a modified protein which has the same function as natural insulin.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main problems commonly encountered during recombinant protein production is protein loss due to protease degradation. We therefore modified the protocol suggested by Pai-Chanfrau and collegues [20] that evaluated the effect of temperature, pH and addition of excess nitrogen source and EDTA, on mini-pro-insulin expression. It was also previously observed that addition of casaminaocids reduced proteolysis of ovin interferon in P. pastoris by acting as preferential substrates [21].…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation experiments were carried out in a Biostat C reactor (Sartorius Stedim; Melsungen, Germany) with initial working volume of 7 L. The medium used for all experiments modified from [20] contained: 20 g/L glycerol, 10 g/L casein hydrolysate, 13.4 g/L YNB, 0.0004 g/L biotin and 100 mM KH 2 PO 4 K 2 HPO 4 salts. Temperature was set at 22 °C, pH was fixed at 6.3 via automated addition of 30% v/v NH 4 OH and 30% v/v H 3 PO 4 .…”
Section: Methodsmentioning
confidence: 99%